Fundamental Understanding and Research Progress on the Interfacial Behaviors for Potassium‐Ion Battery Anode. Issue 20 (9th May 2022) - Yuan, Fei; Li, Zhaojin; Zhang, Di; Wang, Qiujun; Wang, Huan; Sun, Huilan; Yu, Qiyao; Wang, Wei; Wang, Bo
Abstract: Potassium‐ion batteries (PIBs) exhibit a considerable application prospect for energy storage systems due to their low cost, high operating voltage, and superior ionic conductivity. As a vital configuration in PIBs, the two‐phase interface, which refers to K‐ion diffusion from the electrolyte to the electrode surface (solid–liquid interface) and K‐ion migration between different particles (solid–solid interface), deeply determines the diffusion/reaction kinetics and structural stability, thus significantly affecting the rate performance and cyclability. However, researches on two‐phase interface are still in its infancy and need further attentions. This review first starts from the fundamental understanding of solid–liquid and solid–solid interfaces to in‐depth analyzing the effect mechanism of different improvement strategies on them, such as optimization of electrolyte and binders, heterostructure design, modulation of interlayer spacing, etc. Afterward, the research progress of these improvement strategies is summarized comprehensively. Finally, the major challenges are proposed, and the corresponding solving strategies are presented. This review is expected to give an insight into the importance of two‐phase interface on diffusion/reaction kinetics, and provides a guidance for developing other advanced anodes in PIBs. Abstract : This review first starts from the fundamental understanding of solid–liquid and solid–solid interfaces to in‐depth analyzing the effect mechanism of different improvement strategies on them, such as optimization of electrolyte and binders, heterostructure design, modulation of interlayer spacing, etc. Afterward, the major challenges are proposed, and the corresponding solving strategies are presented.